The panhispanista vision of Javier Fernández Pesquero on the hispanic-chilean relations of beginning of the 20th century - Carrellán Ruiz, Juan Luis (Estudios Internacionales, 2016)
The Spanish journalist Javier Fernández Pesquero resided in Chile between 1903 and 1947. During this time he worked at various newspapers as director of some of them. Conservative and nationalist, his thinking is part of panhispanismo, current hispanoamericanismo, which had set an objective that Spain «reconquer» spiritually to its former colonies through moral leadership. Fernández Pesquero followed the dynamics of relations between Spain and Chile leaving their reflections in their reporting. We selected for this research published in the Andalusian magazine La Rábida during the years of World War I in the highlights the problems observed and provides proposals to improve bilateral relations.